The Rights of Spring : A Memoir of Innocence Abroad - Kennedy, David, 1954- (Book collections on Project MUSE., 2009)
Ana reported being blindfolded, doused in cold water. She was tied to a metal frame; electrodes were fastened to her body. Someone cranked a hand-operated generator. One spring more than twenty years ago, David Kennedy visited Ana in an Uruguayan prison as part of the first wave of humanitarian activists to take the fight for human rights to the very sites where atrocities were committed. Kennedy was eager to learn what human rights workers could do, idealistic about changing the world and helping people like Ana. But he also had doubts. What could activists really change? Was there something.